Age effects on the neural processing of object-context associations in briefly flashed natural scenes. (January 2020) - Rémy, F.; Vayssière, N.; Saint-Aubert, L.; Bacon-Macé, N.; Pariente, J.; Barbeau, E.; Fabre-Thorpe, M.
Abstract: In daily life, fast visual recognition of surrounding objects is facilitated through context-based expectations. However the ability to rapidly and accurately recognize unexpected stimuli in a given environment is also crucial and this ability is impaired with age. The present fMRI study aimed at comparing in young and older adults the neural correlates of fast object processing. Patterns of cerebral activity were investigated in response to briefly-presented (100 ms) congruent and incongruent natural scenes. Participants were slower and less accurate when categorizing objects in incongruent relative to congruent contexts. This behavioral cost was notably more pronounced in the older group. Height and multivariate patterns of fMRI activity in context-selective regions were equivalent in both age groups, suggesting preserved processing of coarse scene features in older participants. Incongruent scenes elicited additional activity in the parahippocampal gyrus that possibly reflected simultaneous activation of rarely co-occurring neural representations. Contextual effects were observed in object-selective cortex for the young group only, and may be driven by detection of mismatch between actually perceived and previously-experienced associations. In the older group exclusively, increased bilateral prefrontal and left fusiform activity in response to incongruent scenes was observed. However this supplemental activity was not found to efficiently contribute to improve task performance in difficult visual conditions. Altogether these results suggest age-related changes in the interaction between object- and context-processing pathways, that may subserve impairment in fast identification of unexpected objects in natural scenes. Highlights: Older adults were impaired when rapidly processing unexpected objects in scenes. Processing of coarse context features may stay preserved with age. Older adults' contextual effects in object-selective regions were reduced. Age-related frontal activity increase did not contribute to improve performance.